Description of the larvae of three species of the genus Mordellistena (Coleoptera: Mordellidae) with notes on their ecology - Zemoglyadchuk, Aleksei; Buialska, Nataliia (Zootaxa, 2020)
The mature larvae of Mordellistena luteipalpis Schilsky, 1895, M. koelleri Ermisch, 1956 and M. brevicauda (Bohemann, 1849) are described for the first time. The descriptions are illustrated with photographs of habitus and drawings of the key characters of the larvae. The larva of M. brevicauda differs significantly from the other known larvae of Mordellistena species by fused apical processes and 2-segmented antennae. Ecological data of all three species are presented and discussed. M. luteipalpis is recorded for the first time from Ukraine and Belarus.